(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2022)
The Dayaks, despite being the majority population in Sarawak, were unable to avoid involvement in the communist movement in the 1960s in East Malaysia. Faced with difficulties in obtaining aid and support in the First Division of Sarawak, Kuching, the communists moved to the Third Division of Sarawak (Rajang) which was inhabited by many Dayaks, with the objective of obtaining help for their activities. The current study, based on a qualitative method of collecting and analysing primary and secondary archival sources, found that the communists realised the Dayaks were important in mobilising their activities in Sarawak. The Dayak settlements, concentrated in the rural areas, were not easily detected by the authorities. And it was difficult for the government and security forces to be in contact with the Dayaks due to communication system problems. The study also found that the communists used various strategies to attract Dayaks’ attention and participation in their movement. They befriended the Dayak people by learning their language and culture, by establishing family ties with them, by championing their interests and by promoting their integration with other races. Despite this, the communist movement was not well-received by the Dayaks. Orang Dayak yang merupakan penduduk majoriti di Sarawak juga tidak dapat lari daripada gerakan komunis. Kajian ini bertujuan untuk membincangkan kepentingan dan pelibatan orang Dayak dalam gerakan komunis dan strategi komunis dalam menarik penyertaan mereka. Pada tahun 1960-an, komunis berdepan dengan masalah mendapatkan bantuan dan sokongan di Bahagian Pertama Sarawak iaitu Kuching. Dalam keadaan itu, komunis beralih ke Bahagian Ketiga Sarawak (Rajang) yang dihuni oleh ramai orang Dayak. Komunis berharap golongan ini dapat membantu kegiatan mereka. Kajian ini disempurnakan dengan menggunakan kaedah kualitatif iaitu mengumpul dan menganalisis sumber primer serta sekunder dari arkib dan perpustakaan di Kuala Lumpur serta Kuching. Kajian ini mendapati komunis menyedari orang Dayak adalah penting dalam menggerakkan kegiatan mereka di Sarawak. Petempatan orang Dayak yang tertumpu di kawasan pedalaman tidak mudah dikesan oleh pihak berkuasa. Mereka juga sukar dihubungi oleh pihak kerajaan dan pasukan keselamatan kerana masalah sistem perhubungan. Justeru, komunis menggunakan pelbagai strategi untuk menarik perhatian dan penyertaan mereka. Komunis mendampingi masyarakat Dayak dengan mempelajari bahasa dan budaya, menjalin ikatan kekeluargaan, memperjuangkan kepentingan serta menggalakkan penyatuan mereka dengan kaum lain. Walaupun demikian, gerakan komunis kurang mendapat sambutan dalam kalangan orang Dayak.